Growing the high-resistive Cd₁₋xZnxTe single crystals from a vapor phase - Feychuk, P.; Kopyl, O.; Pavlovich, I.; Shcherbak, L. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
A modified vapor phase growth method to obtain high-resistive Cd1-xZnxTe single crystals (0 < x < 0.13) is presented. The single crystals (about 25 cm⁻³ in size) with natural faceting were grown by vapor transport in silica ampoules with a special shape using a polycrystalline ingot as initial source material. It is shown that minimization of plastic deformation effect in preparation of the most structurally perfect crystals is possible by a way of heat removal from the crystallization front by radiation. The growth of high-resistive material required careful preparation of the initial charge with close to stoichiometric composition. The obtained crystals were successfully tested for creating the room temperature X-ray and gamma-ray detectors.